Disc Forming by Friction Stir Consolidation of AA2024 Chips - Saeb Nazim Abdul Wahed; Sabah Khammass Hussein; Moneer H. Al-Saadi (Journal of Techniques)
This work aims to form a disc by recycling AA2024 chips using friction stir consolidation (FSC) technique. Initially, the chips were compacted inside a chamber by an applied pressure of 20.7 MPa. Different chips weights and two process parameters were studied in the FSC process: pre-heating time and plunging depth of the tool. The process was carried out at 1400 RPM. Effect of the process parameters and chips weight on chips quality was analyzed by design of the experiments method. The discs formed with a fully consolidated (FC) volume fraction range of 14.5-22.4%. The plunging depth was the most effective factor on surface finishing and grain size of the discs, while the chips weight was the most effective factor on the FC volume. Increasing the chips weight and plunging depth increased the FC volume. The average grain size of the disks ranged between 6.3 to 11 mm.